Imagining Dewey : artful works and dialogue about Art as experience - Maarhuis, Patricia L.; Rud, A. G., 1953- (Doing arts thinking, 2021)
Imagining Dewey' features productive (re)interpretations of 21st century experience using the lens of John Dewey's 'Art as Experience', through the doubled task of putting an array of international philosophers, educators, and artists-researchers in transactional dialogue and on equal footing in an academic text. This book is a pragmatic attempt to encourage application of aesthetic learning and living, ekphrasic interpretation, critical art and agonist pluralism.0There are two foci: (a) Deweyan philosophy and educational themes with (b) analysis and examples of how educators, artists, and researchers envision and enact artful meaning making. This structure meets the needs of university and high school audiences, who are accustomed to learning about challenging ideas through multimedia and aesthetic experience.00Contributors are: James M. Albrecht, Adam I. Attwood, John Baldacchino, Carolyn L. Berenato, M. Cristina Di Gregori, Holly Fairbank, Jim Garrison, Amanda Gulla, Bethany Henning, Jessica Heybach, David L. Hildebrand, Ellyn Lyle, Livio Mattarollo, Christy McConnell Moroye, Maria-Isabel Moreno-Montoro, Maria Martinez Morales, Stephen M. Noonan, Louise G. Phillips, Scott L. Pratt, Joaquin Roldan, Leopoldo Rueda, Tadd Ruetenik, Leisa Sasso, Bruce Uhrmacher, David Vessey, Ricardo Marin Viadel, Sean Wiebe, Li Xu and Martha Patricia Espiritu Zavalza.